Talent management and its role in achieving strategic success: An applied study at the General Company for Trading Cars and Machinery/Al-Waziriyah - Nassrullah Khamees Alhamadani, Hanaa (Iraqi Journal for Administrative Sciences, 2026)
This research aims to analyze the role of talent management in achieving strategic success at the General Company for Trading in Cars and Machinery/Al-Waziriyah, through an applied study on a sample of (61) managers and officials from the upper and middle management levels within the company. The research adopted a descriptive-analytical approach to measure the nature of the relationship between the study variables. The dimensions of talent management were defined as four main components: talent acquisition, talent development, talent performance evaluation, and talent retention, with strategic success representing the dependent variable. Data were collected using a questionnaire designed according to scales adopted in management literature and were analyzed using appropriate statistical software to test the research hypotheses. The results showed a significant positive correlation and influence between talent management and strategic success, indicating that adopting effective practices in attracting, developing, evaluating, and retaining talented individuals directly contributes to enhancing the company's competitiveness and achieving its strategic objectives. The research also recommended the necessity of adopting integrated talent management policies within the company's strategic plans to ensure the sustainability of success and improve organizational performance.